2020
DOI: 10.1111/jcmm.15732
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐130a regulates neurological deficit and angiogenesis in rats with ischaemic stroke by targeting XIAP

Abstract: MicroRNAs (miRNAs) have already been proposed to be implicated in the development of ischaemic stroke. We aim to investigate the role of miR‐130a in the neurological deficit and angiogenesis in rats with ischaemic stroke by regulating X‐linked inhibitor of apoptosis protein (XIAP). Middle cerebral artery occlusion (MCAO) models were established by suture‐occluded method, and MCAO rats were then treated with miR‐130a mimics/inhibitors or/and altered XIAP for detection of changes of rats’ neurological function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In this study, we selected CD31 and α-SMA immuno uorescence double staining to label neovascularization in the penumbra region of cerebral ischemia cortex [40].CD31 and α-SMA are markers of vascular endothelial cells and smooth muscle cells, respectively, and are favorable evidence for tube formation and migration into arteries [41]. We found that compared with MCAO group, the number of new blood vessels in DHA group was signi cantly increased, while the number of new blood vessels in GSK0660 inhibitor group was signi cantly decreased compared with DHA group (all P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we selected CD31 and α-SMA immuno uorescence double staining to label neovascularization in the penumbra region of cerebral ischemia cortex [40].CD31 and α-SMA are markers of vascular endothelial cells and smooth muscle cells, respectively, and are favorable evidence for tube formation and migration into arteries [41]. We found that compared with MCAO group, the number of new blood vessels in DHA group was signi cantly increased, while the number of new blood vessels in GSK0660 inhibitor group was signi cantly decreased compared with DHA group (all P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…High miR-130a levels alleviated cardiac dysfunction and cerebral damage by modulating the PTEN/PI3K/AKT axis 27,28 or targeting the X-linked inhibitor of apoptosis protein 12 to prolong MACCE-free survival in ESRD patients. Nonetheless, there were several limitations in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that microRNA-130a (miR-130a) exerts myocardial-protective and neuroprotective effects in vitro and in vivo. 12,13 For example, in in vivo conditions, miR-130a relieves neuronal injury and facilitates neuronal brain tissue growth by downregulating phosphatase and tensin homologous protein (PTEN) expression and upregulating the phosphatidylinositol 3-hydroxy kinase (PI3K) and protein kinase B (Akt) signaling pathways in rats with intracerebral hemorrhage. 14 In addition, miR-130a alleviates human coronary artery endothelial cell injury by inhibiting PTEN expression and activating the PI3K/Akt/endothelial nitric oxide synthase signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…However, Deng et al reported opposite effects of miR-130a in MCAO models. They verified that miR-130a was increased in the brains of MCAO model rats and OGD-treated neurons [ 34 ]. In these animal models, suppressed miR-130a improved neurological function and alleviated nerve damage.…”
Section: Major Mirnas In Hypoxic Signaling and Oxidative Stressmentioning
confidence: 98%